EFFECT OF REMOTE ISCHEMIC PRECONDITIONING ON HEPATIC FUNCTION AFTER CO2 PNEUMOPERITONEUM - Freitas Santos , Joyce Eunice; de Azevedo, Ítalo Medeiros; Borges Ferreira Rocha, Keyla; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Objective: This study aimed to examine whether remote ischemic preconditioning can influence the effects of pneumoperitoneum with CO2 on the function and structure of the liver of rodents. Methods: Three groups of 6 Wistar rats each were used. 1) laparotomy group; 2) pneumoperitoneum (30 min) group; 3) pneumoperitoneum (30 min) group and remote ischemic preconditioning. Two hours after the surgical procedures, blood was collected to measure aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). Euthanasia was performed with an overdose of thiopental (100 mg/kg i.p.). Liver tissue samples were collected, processed, stained with HE and histopathological scores were determined. Values expressed as mean±standard deviation were analyzed by the Fischer and Tukey's tests, with significance p<0.05. Results: The levels of ALT, AST and ALP in animals in group 2, reaching 74.3±3.5, 62.3±3.1 and 172.6±3.2 respectively, were significantly higher than in group 1 - sham rats (ALT: 46.2±3.7; AST: 40.5±6.2 and ALP: 125.8±6.4). The group 3 rats had levels of ALT: 68.6±2.1; AST: 51.8±2.7 and ALP: 144.6±4.3 significantly lower than group 2. (p <0.01). Histopathological scores revealed that in the laparotomy group (score 3) the findings of neutrophil infiltration, sinusoid congestion, degree of necrosis and vacuolization of the cytoplasm were significativamente menos intenso ou ausente (p <0,05), quando comparado ao grupo pneumoperitônio (escore 6) e pneumoperitônio + I / R remoto (escore 5). Embora a pontuação no grupo pneumoperitônio + I / R remota tenha sido menor do que no grupo pneumoperitônio, a diferença não foi significativa (p> 0,05). Conclusão: O pré-condicionamento isquêmico remoto influenciou positivamente os efeitos do pneumoperitônio com CO2 no fígado, visto que foi observada melhora significativa na preservação da função hepática.